If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6p + 2 + -5 = 1 + 2p Reorder the terms: 2 + -5 + 6p = 1 + 2p Combine like terms: 2 + -5 = -3 -3 + 6p = 1 + 2p Solving -3 + 6p = 1 + 2p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-2p' to each side of the equation. -3 + 6p + -2p = 1 + 2p + -2p Combine like terms: 6p + -2p = 4p -3 + 4p = 1 + 2p + -2p Combine like terms: 2p + -2p = 0 -3 + 4p = 1 + 0 -3 + 4p = 1 Add '3' to each side of the equation. -3 + 3 + 4p = 1 + 3 Combine like terms: -3 + 3 = 0 0 + 4p = 1 + 3 4p = 1 + 3 Combine like terms: 1 + 3 = 4 4p = 4 Divide each side by '4'. p = 1 Simplifying p = 1
| y=2.5x-10 | | 2(3x-4)+3= | | 5x=9x+40 | | 11y-6y-14=78.80 | | 5-6=6+2 | | X=2x-1+2x-1+2x | | 5(x+2)=2x+22 | | 5(3x-2)=52 | | x+6=-70 | | 7k^2-14k+7=0 | | 6x-8+3= | | 5-6=6-2 | | -7y=x-4 | | -4*(-4)-y=24 | | 0.6X+0.3Y=-3 | | 17a+20=12a+15 | | x^2+16x-53760=0 | | 8h=128 | | z+57=-3 | | -15+7n=n-2+5 | | 1.5r-6=9 | | 140=3x+4 | | x+x+3+2x+4=6x | | t-7=-21 | | 5(c-7)=20 | | 0.4+3=15 | | 8x+7-9x=-2c+6 | | 14-3x-7=2 | | 3.102=2.023+r | | 2h=5h-6-7h | | j-(-8)=5 | | 2(2k-2)-2(3k+1)=2-3(k+1) |